(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article delves into the scientific interpretation of the semantic category of state in linguistics, exploring how states are encoded and decoded within various linguistic frameworks. It examines the theoretical underpinnings that define states, distinguishing them from processes and actions. The discussion extends to the role of morphology and syntax in expressing states across different languages, highlighting examples from English, Russian, and Mandarin.